Pemberdayaan Kepala Sekolah dan Guru dalam Mengimplementasikan Program Sekolah Penggerak dan Merdeka Belajar - Marinu Waruwu; Yari Dwikurnaningsih; Bambang Ismanto; Ade Iriani; Sophia Tri Satyawati; Wasitohadi Wasitohadi (Universitas Kristen Satya Wacana Salatiga, 2022)
Community service activities are carried out for school principals and teachers of Kindergarten, Elementary, Middle and High Schools in the city of Salatiga, Semarang Regency, Ambarawa, Boyolali, Nias Islands, Sulawesi, Maluku, Papua and East Nusa Tenggara. This activity aims to equip school principals and teachers in understanding the concepts and practices of implementing the activator school program and free learning curriculum. Activities carried out in the form of online webinars with lecture and discussion methods. The results of community service show that the satisfaction level of participants in the first stage was at a percentage of 93%, in the very satisfactory category, and the satisfaction level of participants in the second stage was at a percentage of 91%, in the very satisfactory category. This shows that the implementation of community service has an impact on increasing participants' knowledge in implementing the activator school program and the independent learning curriculum.